(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the majority of poor nations, corneal disorders rank as the second most common cause of blindness. Large-scale expenditures in basic eye care services and public health infrastructure around the world have created a solid foundation for preventing further corneal blindness. However, there are 4.9 million people with bilateral corneal blindness who could potentially need a corneal transplant in order to regain their vision. Increased corneal transplantation has historically faced formidable obstacles, including high costs and logistical impossibilities due to the scarcity of trained corneal surgeons and limited tissue availability. Now that cataract surgery rates are rising and some Asian and African nations have more developed eye care systems, there is a strong foundation from which to significantly increase corneal transplantation rates